2019
DOI: 10.1111/jtxs.12386
|View full text |Cite
|
Sign up to set email alerts
|

Quality and microbial properties of symbiotic bread produced by straight dough and frozen part‐baking methods

Abstract: Symbiotic bread was produced by straight dough and frozen part‐baking methods using inulin as a prebiotic (0–7.5% in straight dough method and 5% in frozen part baked bread) and GanedenBC 30 as a probiotic. With addition of inulin, dough water absorption and softening reduced, but dough development time and stability time increased. Inulin prevented excessive moisture loss during bread storage and enhanced crust darkness and crumb firmness while reduced bread volume. Increasing the frozen storage time (up to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
0
9
0
2
Order By: Relevance
“…This protection has been proven, Sohail et al showed that the double-layer spray drying microcapsules of L. acidophilus NCFM helped maintain 5.51 log CFU/g after 6 months of storage at 4℃ [16]. The presence of both prebiotic and probiotic formed a symbiotic system [7]. therefore L. plantarum seemed to have access to the carbon source for their development (Fig.…”
Section: Survey Of Refrigerating Storagementioning
confidence: 91%
See 1 more Smart Citation
“…This protection has been proven, Sohail et al showed that the double-layer spray drying microcapsules of L. acidophilus NCFM helped maintain 5.51 log CFU/g after 6 months of storage at 4℃ [16]. The presence of both prebiotic and probiotic formed a symbiotic system [7]. therefore L. plantarum seemed to have access to the carbon source for their development (Fig.…”
Section: Survey Of Refrigerating Storagementioning
confidence: 91%
“…But it is worth noting that most of the probiotic supplement foods on the market are made from dairy sources, such as ice cream, cheese, yogurt, and more. Meanwhile, the demand for non-dairy products is increasing according to vegetarianism or health issues related to dairy products such as lactose intolerance, allergies with milk protein and blood cholesterol control [7]. Therefore, probiotic bakery products contained probiotic microorganism is considered a new trend as well as diversify choice for probiotic supplement products.…”
Section: Introductionmentioning
confidence: 99%
“…In their research, Almada-Érix et al (2022) proved that the probiotic Bacillus coagulans added to bread showed high resistance to the baking process and was above 10 7 CFU/g. Majzoobi et al (2019) in the results of their study showed that in the production of symbiotic bread an acceptable number of GanedenBC30 (more than 10 6 CFU/g) was obtained even after storage for 3 days at room temperature.…”
Section: Introductionmentioning
confidence: 97%
“…However, the application probiotic in food products are limited and currently provided by dairy products such as yogurt (Adhikari et al, 2000), mayonnaise (Lieu et al, 2017), skim milk Maciel et al, (2014), cheese and so on, and have few studies on bakery products, a nondairy products. Besides, dairy products also cause lactoseintolerant (Majzoobi et al, 2018). Moreover, the price of dairy products makes the consumers who live in third-world countries are limited in consumption.…”
Section: Introductionmentioning
confidence: 99%
“…In the opposite view, the loading directly probiotic in the dough before baking will give more choices that can be chosen by the target consumer. However, the heat sensitivity of probiotic bacteria leading to the inactivation that occurs during baking decreased the viability of probiotic (Majzoobi et al, 2018;Arslan et al, 2018). Microencapsulation techniques are the method to help probiotic organisms against the disadvantaging effect of the outside environment (González -Forte et al, 2014; Lieu et al, 2017;Zhang et al, 2018;Muzzafa et al, 2018;Arslan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%